Feminist foreign policy: Concepts, core components and controversies - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2022)
In their Coalition Agreement 2021-2025, the parties that form the current German government agreed to pursue a "Feminist Foreign Policy" (FFP). The German Foreign Office is now committed to do so, while the Federal Ministry for Economic Cooperation and Development seeks to pursue a "feminist development policy". FFP will also be a discussion topic in Germany's first National Security Strategy. Germany is thus following a trend, as ever more governments commit to FFP or at least seek to realise certain elements. Yet what the FFP approach actually means in theory and practice remains vague and contentious: what preconditions it requires, in what contexts it applies and what implications it involves. This openness provokes debates across politics, civil society and academia. Although the national implementations of FFP only very partially realised feminist demands, the mere fact of official policy referencing feminism challenges traditional ways of thinking and political patterns, encourages reassessment of political priorities and their coherence, and can potentially promote political innovation.
Keywords: 320